2017
DOI: 10.1177/1086026617717456
|View full text |Cite
|
Sign up to set email alerts
|

Stages of Corporate Sustainability: Integrating the Strong Sustainability Worldview

Abstract: Businesses are increasingly adopting sustainability, yet the environment continues to decline. This research responds to Dyllick and Muff’s assertion that this paradox is caused by a constricted understanding of the meaning of corporate sustainability, lack of inclusion of constructs from related streams of literature, and failure to integrate micro and macro perspectives of sustainability. The current research addresses these concerns through an integration of 22 micro- and macro-level models of stages of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
248
0
23

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(273 citation statements)
references
References 77 publications
(141 reference statements)
2
248
0
23
Order By: Relevance
“…Although businesses are increasingly adopting issues of sustainability, the environment continues to decline (Landrum, ). One reason may be that businesses still operate on 19th‐century paradigms, which are only superficially updated to include the problems of sustainability (Starik, Stubbs, & Benn, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although businesses are increasingly adopting issues of sustainability, the environment continues to decline (Landrum, ). One reason may be that businesses still operate on 19th‐century paradigms, which are only superficially updated to include the problems of sustainability (Starik, Stubbs, & Benn, ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there is a general ‘big disconnect’ between companies' current approaches to environmental management and those required of them (Dyllick & Muff, , p.157; Landrum & Ohsowski, ; Milne & Gray, ); companies' environmental management approaches generally fall short of those required for the sustainability of the natural environment (Haffar & Searcy, ). Scholars have therefore called for a shift from currently‐practiced incremental approaches to the adoption of radical approaches to environmental management (Landrum, ) that enhance the sustainability of the natural environment. Scholars have, furthermore, suggested that self‐regulation, government regulation and civil society pressure can be used to improve sustainability management (Karnani, ).…”
Section: Introductionmentioning
confidence: 99%
“…The corporate sustainability movement is facing a seeming paradox: Despite the growing infusion of environmental concerns into corporate strategy over the last decades, the degree of planetary ecological degradation continues to increase (Dyllick & Muff, ; Landrum, ). On the one hand, some firms are achieving resource productivity improvements, contributing to a partial decoupling of growth from material consumption in developed countries (Plank, Eisenmenger, Schaffartzik, & Wiedenhofer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing infusion of environmental concerns into corporate strategy over the last decades, the degree of planetary ecological degradation continues to increase (Dyllick & Muff, 2016;Landrum, 2018).…”
Section: Introductionmentioning
confidence: 99%